Cruise tourism: a hedonic pricing approach. Issue 1 (24th January 2018) - Espinet-Rius, Josep Maria; Fluvià-Font, Modest; Rigall-Torrent, Ricard; Oliveras-Corominas, Anna
Abstract : Purpose: The purpose of this paper is to examine the effect on price of different cruise industry characteristics from the point of view of actual prices. The analysis is carried out from the supply side but taking into account the real prices paid by customers. Design/methodology/approach: This paper uses the hedonic price methodology. To develop this research, a database of more than 36, 000 prices paid by cruise passengers and different characteristics of ships in 2013 was built. To obtain the results, ten models have been developed with significant adjusted R 2 of between 0.85 and 0.93 making the models and results robust. Findings: The results show that the main attributes affecting prices are the number of nights of the itinerary, the departure date, the number of days before departure the booking is made, the accommodation type and some facilities, such as casinos, cinemas and swimming pools. The results also yield a ranking of ship companies based on price and quality dimensions. Finally, the authors suggest some implications for management and new research. Originality/value: This paper offers a new approach in the academic literature of the cruise industry in two respects. First, in its use of a broad database of actual prices paid by passengers – more than 36, 000 observations. Second, in the application of the hedonic pricing methodology, widely used in the tourism sector (see the Methodology and Database section) but until now not in the cruising segment.